Sudden Bilateral Sensorineural Hearing Loss Secondary to Cerebral Venous Thrombosis with a Complete Recovery - Muhammad Nu’aim, Ishak; Nik Mohd Syukra, Nik Abdul Ghani; Irfan, Mohamad (2018)
Introduction: Sudden sensorineural hearing loss (SSNHL) is an important otological emergency. Up to 90% of the cases are idiopathic. Cerebral venous thrombosis (CVT) is an extremely rare identifiable cause as it only represents 0.5% of all strokes. Case Report: In this paper, an unusual case of bilateral SSNHL secondary to bilateral CVT with rapid and complete recovery is reported. The patient presented with sudden bilateral hearing loss associated with some neurological symptoms. Initial computed tomography (CT) venography revealed a CVT of bilateral transverse sinuses. The patient was started on an anticoagulant and imaging was repeated after five days, revealing the absence of the thrombosis. Serial pure tone audiometry (PTA) showed complete recovery of bilateral hearing within 10 days. Conclusion: Early detection and intervention may fasten hearing recovery and improve the quality of life. The immediate restoration of venous blood flow and intracranial pressure may lead to the complete recovery of bilateral hearing loss.